CORPORATE SOCIAL RESPONSIBILITY, CORPORATE PERFORMANCE, AND MODERATING EFFECT OF OWNERSHIP CONCENTRATION IN INDONESIAN COMPANIES - Itan, Iskandar; Ang, Meiga Putri Antoni; Butar-Butar, Dea Tiara Monalisa (Universitas Multimedia Nusantara, 2024)
Abstract” Corporate Social Responsibility (CSR) is a necessity that needs to be implemented so that companies operate not only for the benefit of shareholders but also for the public, government, consumers, the environment, and other stakeholders. CSR is also one of the management models that has been implemented in Indonesia, making it an alternative management model. The purpose of this research is to investigate the impact of social responsibility disclosure on corporate performance and the moderating effect of ownership concentration in this relationship. The data collection technique for this research uses secondary data, meaning data obtained from other sources by extracting information from the annual reports and sustainability reports of companies listed on the Indonesia Stock Exchange (IDX). The testing is done using E-Views. The results of this research indicate that CSR disclosure has a significant negative effect on financial performance, measured by both return on assets (ROA) and Tobin's Q. Ownership concentration plays a moderating role in strengthening the relationship between CSR and ROA, but it does not play a moderating role in the relationship between CSR and Tobin's Q. Keywords: Corporate Performance; Ownership Concentration; Corporate Social Responsibility